Static Aeroelastic Modeling and Rapid Analysis of Wings in Transonic Flow - Jingyuan Yang; Yilang Liu; Weiwei Zhang (International Journal of Aerospace Engineering)
A fast static aeroelastic analysis method, coupling with the modal method and Kriging surrogate model, is proposed in this paper. The deflection of the wing is described by the modal method, and the Kriging surrogate model is utilized to model the generalized forces under different deformations, angles of attack, and Mach numbers in order to replace the CFD solver. We analyzed the static aeroelasticity of HIRENASD wing in transonic flow field by coupling with the generalized force model by the static equilibrium equation. The results were compared with those of the experimental data and the references, and the comparison shows that the method is useful for the small deflections. After enough training cases are finished, the high-accuracy aerodynamic force coefficients and wing deflection will be obtained rapidly, which will only take several seconds. This method is more time saving than the CFD/CSD method, when it comes to a large quantity of the static aeroelastic analyses. Hence, it has good perspective for engineering applications during the aircraft design period.